Know-How - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2004)
In daily life we not only speak not only of knowing facts but also of know-how. We may not only judge that someone knows that the stock market is in decline, that an avalanche is imminent or that ice is not marble but also that someone knows how to make money on the stock exchange, knows how to survive an avalanche or knows how to carve a realistic life-sized human figure from a block of marble. Ryle (1949, 26-60) first drew attention to analysis of know-how and argued that know-how does not consist of propositional knowledge. He went on to give an analysis of know-how. Since then the analysis of propositional knowledge has largely overshadowed that of know-how. However there has been a resurgence of interest in it. For example, relatively recent proposals in philosophy of mind and ethics proceed in terms of know-how. For example, in response to Frank Jackson’s knowledge argument, David Lewis replies that knowing what an experience is like is a matter of knowing how to recognise, remember and imagine it. Hilary Putnam claims (1996, xvi) that “knowing the meaning of the word ‘gold’ or of the word ‘elm’ is not a matter of knowing that at all, but a matter of knowing how”. A more specific variant on this claim is Michael Devitt’s (1966, 173) conclusion that someone who knows the meaning of a term knows how to use it with a certain meaning but that such a person need not have ‘any propositional knowledge about what constitutes its meaning’.